A Comparison of Scientific Productions of Iran with Competitor Countries in the Middle East in the Field of Education - Mohsen Nazarzadeh Zare; Ehsan Jamali; Mohammad Ali Arein; Ramtin Skrouchi; Ali Reza Nasiri Firuz (مجله علم‌سنجی کاسپین, 2014)
Background and aim: The aims of this study was to compare the scientific productions of Iran in the field of education with competitor countries in the Middle East (Turkey, Saudi Arabia, Pakistan, Egypt and Israel) based on published articles in the Web of Science database from 2003 to 2012.